THE EFFECT OF GIVING HOT GINGER DRINK AND HOT LIME DRINK TOWARD EMESIS GRAVIDAE - Rahajeng Siti Nur Rahmawati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2018)
Nausea and vomiting happen on 60%-80% primigravida and 40%-60% multigravida. One hundred of a thousand symptoms of nausea in pregnancy will be heavy if the treatment is not good. Emesis Gravidarum is a normal grievance which is experienced by pregnant mother in first trimester and can become hyperemesis gravidarum so that it increases the risk of disorders of pregnancy. Nausea and vomiting in pregnancy can be avoid with pharmacology and nonpharmacologic therapy. One of nonpharmacologic therapies to control nausea and vomiting is ginger and lime. This research aimed to prove the effects of hot ginger drink and hot lime drink to first semester pregnant mother in Puskesmas Grogol, Kediri District. This research used experiment queasy study of pre-posttest design in group of hot ginger drink and hot lime drink. The population was all pregnant mothers in first semester who experienced emesis gravidarum in Puskesmas Grogol, Kediri District. The samples were 32 people by using purpose sampling technique. Collecting the data was conducted directly through the observation. Data analysis used statistic test of Wilcoxon Match Test and Mann Whitney U Test. The result of the study before and after giving hot lime drink showed that the score was p = 0,002 (p < 0,05), so H1 was achieved and H0 was ignored, it meant there was effect of giving hot lime drink toward emesis gravidae in Puskesmas Grogol, Kediri District. Data analysis used statistic test of Mann Whitney U Test resulted U number > U table = 118.5 > 66 so H0 was achived. H1 was ignored, it meant there wes not different significance between giving hot ginger drink and hot lime drink toward the decrease of emesis gravidarum. The conclusion of this research shows that hot ginger drink and hot lime drink are effective in decreasing emesis gravidarum so that people get the benefit from hot ginger drink and hot lime drink as alternative medicine before consuming antiemetic medicine. They can also make the variants of ginger and lime to decrease the frequency of emesis gravidarum because they are easy to get, simple and effective without side effects and they do not harm mother and the fetus.